"It's changed my life!" Evaluation and improvement of a pilot Tier 2 weight management course, "Balance". Issue 1 (30th January 2021) - McGuire, Sally; Stephens, Alex; Griffith, Emma
Abstract : Purpose: This paper aims to describe a service evaluation study of "Balance" – a National Health Service Tier 2 pilot weight management course delivered in a primary care mental health service. The 12 weekly sessions included dietetic, psychological and behavioural elements underpinned by cognitive behavioural theory and "third-wave" approaches, including acceptance and commitment therapy, compassion-focused therapy and mindfulness. Design/methodology/approach: A mixed-methods design was used in this service evaluation study that included analysis of outcome measures (weight, eating choices, weight-related self-efficacy and mental health) and focus group data ( n = 6) analysed using thematic analysis. Eleven clients with a body mass index of 25–40 kg/m 2 enrolled, and nine clients completed the course. Outcome data were collected weekly with follow-up at three and six months. Findings: Quantitative data analysis using non-parametric Wilcoxon signed-rank tests showed that the group mean weight decreased significantly ( p = 0.030) by the end of Balance, but the group mean weight loss was not statistically significant at the three-month ( p = 0.345) or six-month ( p = 0.086) follow-up. The qualitative results showed that participants valued the course ethos of choice and also welcomed learning new tools and techniques. Balance was very well-received by participants who reported benefitting from improved well-being, group support and developing new weight management skills. Research limitations/implications: Only one client attended all sessions of the group, and it is possible that missed sessions impacted effectiveness. Some of the weight change data collected at the six-month follow-up was self-reported ( n = 4), which could reduce data reliability. Focus group participants were aware that Balance was a pilot with a risk that the group would not be continued. As the group wanted the pilot to be extended, the feedback may have been positively skewed. A small sample size limits interpretation of the results. A group weight management intervention, including dietetic, psychological and behavioural elements, underpinned by cognitive behavioural theory was well-received by service users and effective for some. Commissioners and service users may have different definitions of successful outcomes in weight management interventions. Practical implications: Longer-term support and follow-up after Tier 2 weight management interventions may benefit service users and improve outcomes. Originality/value: The paper contributes to a small but growing evidence base concerned with the design and delivery of weight management interventions. Areas of particular interest include: a gap analysis between the course content and National Institute for Health and Care Excellence clinical guidelines, participants' views on the most impactful course features and recommendations for course development. The results also show a disconnect between evidence-based guidelines (mandatory weight monitoring), participants' preferences and clinicians' experience. The difference between client and commissioner priorities is also discussed.